A voz na construção de personagens em um desenho animado - Crochiquia, Alice (2020)
Attributing personality and attitude traits based on a speaker's voice has permeated human relationships since Ancient history (Kreiman and Sidtis, 2011). Within a specific cultural and linguistic context and shared by a group of listeners, these attributions of certain characteristics to a speaker reflect vocal stereotypes, which refer to the relations between sound and meaning established in expressive speech. Given this context, our study comprises an experimental investigation approach of expressive speech that integrates methodological procedures of perceptual and acoustic analyses. As the object of study, we have chosen voice quality, that performs linguistic, extralinguistic and paralinguistic functions. The latter is the focus of our study. Speech samples from the four main personality-distinct characters in the animated feature film Zootopia dubbed by Brazilian voice actors have been analyzed. Due to the expressive function of voice quality, we have posed two questions: Which vocal quality settings were used by the actors in the film to compose the profile of the characters? What acoustic characteristics do these settings display? For the study, two hypotheses were formulated: the voice quality and vocal dynamics profiles of each character are distinct from one another; the correlations between the physical and psychological characteristics and the vocal profiles of each character reflect the patterns described in the sound symbolism codes. Perceptual evaluation of the 54 speech stimuli was performed using the VPA-PB scheme (Camargo & Madureira, 2008), a modified version of the Vocal Profile Analysis Scheme (Laver & Mackenzie Beck) for Brazilian Portuguese. Acoustic measures have been automatically extracted using the ExpressionEvaluatorbySG script (Barbosa, 2008) for PRAAT. The profiles for each of the four characters were composed based on the psychological traits presented throughout the film. The results of the acoustic analysis, the perceptual analysis of voice quality settings were correlated using the MFA (Multiple Factor Analysis) method in the R environment based on 40 variables (quantitative and qualitative) and it turned out that the speech stimuli were distributed in 6 clusters according to the variables analyzed. The quantitative variables that presented the highest correlation percentage were: Standard deviation of f0 derivative, Standard deviation of spectral tilt, f0 Median. The qualitative variables that presented the highest correlation percentage wre: Lowered larynx, Lip rounding, Breathy voice and Minimised pitch range. The research has presented evidence in favor of the symbolic use of phonic matter and contributions to the understanding of how vocal stereotypes are established